2002
DOI: 10.1093/nar/30.4.975
|View full text |Cite
|
Sign up to set email alerts
|

c-Maf, the gammaD-crystallin Maf-responsive element and growth factor regulation

Abstract: The transcription factor c-Maf has been suggested to regulate the activity of gamma-crystallin promoters in lens fibre cells. We here show that the transactivation potential of c-Maf and MafB for the rat gammaD-crystallin Maf-responsive element (gammaD MARE) is dependent upon the cellular context and, using chimeric and single domain mutants, that c-Maf is most likely to be the cognate factor for the gammaD MARE in the lens. Transactivation of the gammaD MARE by c-Maf in lens cells was not enhanced by c-Fos or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…The mechanisms regulating activation of Maf family proteins have been investigated (Gardner and Montminy, 2005) and include a model invoking bFGF/MEK/ERK-induced phosphorylation that triggers proteosome-dependent degradation (Ochi et al, 2003) to explain L-Maf's decreased stability in neural retinal cells. In contrast, inhibition of the MAPK, MEK, increased c-Maf transactivation of the gammaD crystallin gene (Civil et al, 2002), while we observe that a similar MEK inhibition decreases c-Maf transactivation of the CD13 promoter in endothelial cells to a similar extent as mutation of Ser 15 (unpublished observations, Mahoney and Shapiro). Therefore, in endothelial cells the Ras/MAPK signal transduction pathway appears to activate c-Maf and CD13 transcription but inhibits L-Maf (and c-Maf) activity in primary neural retinal cells (Ochi et al, 2003).…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…The mechanisms regulating activation of Maf family proteins have been investigated (Gardner and Montminy, 2005) and include a model invoking bFGF/MEK/ERK-induced phosphorylation that triggers proteosome-dependent degradation (Ochi et al, 2003) to explain L-Maf's decreased stability in neural retinal cells. In contrast, inhibition of the MAPK, MEK, increased c-Maf transactivation of the gammaD crystallin gene (Civil et al, 2002), while we observe that a similar MEK inhibition decreases c-Maf transactivation of the CD13 promoter in endothelial cells to a similar extent as mutation of Ser 15 (unpublished observations, Mahoney and Shapiro). Therefore, in endothelial cells the Ras/MAPK signal transduction pathway appears to activate c-Maf and CD13 transcription but inhibits L-Maf (and c-Maf) activity in primary neural retinal cells (Ochi et al, 2003).…”
Section: Discussionsupporting
confidence: 50%
“…Sequence alignment of the large Maf proteins showed that numerous putative phosphorylation sites in the amino terminal transactivation domain are highly conserved (Civil et al, 2002) a region we find critical for maximal activation of the CD13 promoter in endothelial cells. We chose to focus on two ERK phosphorylation sites which are strictly conserved in all of the large Maf proteins (serines 15 and 70 in the c-Maf sequence, Fig.…”
Section: Putative Phosphorylation Sites Of C-maf Are Differentially Umentioning
confidence: 82%
See 2 more Smart Citations
“…These include the L7 gene in Purkinje cells [14] and the detoxifying enzyme gene quinone oxidoreductase l in hepatocytes [15], which are activated and repressed by c-Maf, respectively. In vitro, c-Maf transactivates the cyclin D2 promoter in myeloma cell lines [16] and the cD-crystallin promoter in lens epithelial cell explants [17]. A novel long form of c-Maf, Lc-Maf, regulates type II collagen via interactions with Sox9 [11].…”
mentioning
confidence: 99%